Drawing the line : using cartoons as historical evidence - Scully, Richard; Scully, Richard (Monash Univ. ePress, 2009)
Drawing the Line: Using Cartoons as Historical Evidence brings together essays from international scholars working with cartoons in their research and teaching. It is a showcase for some of the best recent scholarship in this field, with articles exploring racial and ethnic stereotypes, as well as representations of youth, gender and class across a number of key historical epochs. Cartoons are among the most vivid and familiar images of past politics and opinion, but tend to be used merely as 'illustrations' for historical works. Drawing the Line, however, provides a comprehensive introduction to the study of cartoons as sources in their own right. The British Regency Crisis, post-Civil War US politics, Anglo-Iraqi interaction in the Second World War, and Yugoslav Communist propaganda are just some of the themes through which the effective use of cartoons in historical writing is explored.--About page